Historical Levels of National Values - O'ralovna, Khurramova Gavhar (European Journal of Life Safety and Stability (2660-9630), 2023)
The article provides information about values, the social importance of values, the difference between heritage and values. Today's importance of universal values, national and regional values is highlighted.